The secret keeper - Lewis, Beverly, 1949- (Minneapolis, Minnesota : Bethany House, 2013)
"Jennifer Burns has always had an 'old soul, ' but joining the Amish world will challenge her spirit--and her heart-- in ways she never expected"--Provided by publisher.
Keywords: Amish -- Fiction; Lancaster County (Pa.) -- Fiction; Domestic fiction